2008
DOI: 10.17159/2078-516x/2008/v20i1a292
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness, nutritional habits and daily locomotive action of 12-year-old children with different body mass index

Abstract: Objective. The purpose of this study was to examine the differences in physical fitness, daily nutritional habits and locomotive behaviour among pupils with varying body mass index (BMI) in the 5th and 6th grades of primary school.Design. The sample consisted of 480 pupils (229 boys and 251 girls), who participated in specific Eurofit tests and completed questionnaires probing their physical activity and nutritional habits. They were divided according to their BMI into normal, overweight or obese children.Main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
2
1
2
Order By: Relevance
“…Also except the obese subjects, other counterparts were not different in performing the sit and reach test. Some studies reported no relationship between obesity and flexibility [ 21 , 29 ] , which our results are not accordance with. The results of this study found no differences for flamingo balance among BMI categories which is in agreement with the results of Raudsepp et al [ 24 ] and adversely is in contrast to the results of Deforche et al [ 30 ] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also except the obese subjects, other counterparts were not different in performing the sit and reach test. Some studies reported no relationship between obesity and flexibility [ 21 , 29 ] , which our results are not accordance with. The results of this study found no differences for flamingo balance among BMI categories which is in agreement with the results of Raudsepp et al [ 24 ] and adversely is in contrast to the results of Deforche et al [ 30 ] .…”
Section: Discussioncontrasting
confidence: 99%
“…However, overweight and obese children can perform equally well, such as sit and reach [ 20 , 21 ] and flamingo balance [ 24 ] ; or even better, such as handgrip strength test [ 25 , 26 ] than children with normal weight in those muscular fitness tests where their body does not have to be transported. Higher hand grip strength was found in both overweight and obese subjects than normal weight and underweight subjects, which is in agreement with other studies [ 25 , 26 ] .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have given rise to the development of the second edition of the CAPL (CAPL-2), which is currently suggested to be used as a valid and reliable tool for assessing PL in 8-12 year old children (Longmuir et al, 2018a). In Greece, researchers have documented children's progress in various PL domains by examining the relationships between PA, motor competence and perceived motor competence (Afthentopoulou et al, 2018), daily PA and fitness (Kamtsios and Diggelidis, 2007), participation motives (Papaioannou et al, 2006) or self-perceived motivational climate (Sevdali et al, 2017). However, studies of this kind have been conducted under a more conventional and linear perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados em países em desenvolvimento (Dórea et al, 2008;Nhantumbo et al, 2013)(2 encontraram níveis baixos em alguns indicadores da aptidão física (força, agilidade, salto em distância e agilidade) em adolescentes, quando relacionados com a subnutrição e com elevados valores de massa corporal. (Kamtsios & Digelidis, 2008;Ng, Marshall, & Willows, 2006;Shang, Liu, Hu et al, 2010). Igualmente importante, mas não tão amplamente estudado, é o risco de comprometimento psicológico que se pode apresentar como consequência do excesso de peso em contextos pediátricos (Powel-Young, Zabaleta, VelascoGonzalez, & Sothern, 2013).…”
Section: Introductionunclassified